Controlled synthesis of ZnS quantum dots and ZnS quantum flakes with graphene as a template - Li, Caixia (Langmuir : the ACS journal of surfaces and colloids, 2012)
Novel ZnS quantum dots (QDs) and ZnS quantum flakes (QFs) were successfully prepared with graphene nanosheets (GNs) as a special template, and two unique heterostructures of ZnS/GNs were also obtained. Due to the structure-directing template effect of GNs, the as-synthesized ZnS with different morphologies, dots or flakes, were uniformly distributed on the surface of GNs by controlling nucleation and growth. The two different heterostructures of ZnS/GNs exhibited obvious photovoltaic response, and ZnS/GN QFs-on-sheet heterostructures show higher photovoltage than that of ZnS/GN QDs-on-sheet